Improving Physical Abilities And The Most Efficient Methods In Adults Over 40 Years Old: 10.62591/ajpa.2023.12.02 - Andrea, Kristian; Qeleshi, Anesti; Zotaj, Redon (Arena-Journal of Physical Activities, 2024)
Only a small percentage of adults engage in regular physical activity, which means a decline in quality of life and a very poor result compared to Europe (Osinski, 2013). The purpose of this literature review is to find the most contemporary methods from the most ranked scientific works on the improvement of physical abilities and the most efficient methods in adults over 40 years old. Digital databases such as Scopus, Medline, JStore, Embase, Cochrane Central, PsycInfo, Schoolar, and SPORTDiscus were used in this literature review. Inclusion criteria are: individuals must be healthy and average age at least 40 years old. Many other studies such as (Skelton et al., 1994; Foldvari et al., 2000; Bean et al., 2007) report that physical functions are more related to muscle power than to muscle strength or mass. Strength training has many benefits on physical function in older adults compared to traditional strength training (Tschopp et al., 2011; Da Rosa., 2019). Harmonization or proper use of variables such as exercise selection, breaks, number of sets, number of repetitions, frequency affect the increase in the level of muscular fitness. Strength, muscular endurance, muscular strength and muscular hypertrophy are the characteristics that should be trained (Ratamess et al., 2009). While in an all-inclusive program resistance training improves the cardiovascular system (Fleck. 1988), limits the risk of coronary heart disease (Goldberg. 1989; Hurley & Kokkinos, 1987), helps prevent osteoporosis (Layne & Nelson. 1999), removes the risk of diabetes (Miller et al., 1984), promotes maintaining a healthy weight and losing excess weight (Evans. 1999), reduces the risk of cancer in the spine (Koffler et al., 1992), helps in psychological/mental well-being (Ewart. 1989) as well as improves dynamic stability and maintenance of functional capacity (Evans. 1999). In conclusion from the study of Balachandran et al. (2022) found that strength training leads to improvements in physical function more than traditional strength training.